Predicting, Treating and Preventing Postoperative Recurrence of Crohn’s Disease: The State of the Field - Anna M Borowiec; Richard N Fedorak (Canadian Journal of Gastroenterology)
The majority of patients diagnosed with Crohn’s disease eventually require surgical intervention. Unfortunately, postsurgical remission tends to be short lived; a significant number of patients experience clinical relapse and many require additional operations. The pathogenesis of this postoperative recurrence is poorly understood and, currently, there are no reliable tools to predict when and in whom the disease will recur. Furthermore, the postoperative prophylaxis profiles of available Crohn’s disease therapeutic agents such as 5-aminosalicylates, immunomodulators, steroids and probiotics have been disappointing. Recently, the combination of antibiotics and azathioprine in selected high-risk patients has demonstrated some potential for benefit. The goal of the present article is to provide a coherent summary of previous and new research to guide clinicians in managing the challenging and complex problem of postoperative Crohn’s disease recurrence.